History of the Decline and Fall of the Roman Empire $1 (BVolume 5s - Gibbon, Edward, 1737-1794; Milman, Henry Hart, 1791-1868 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of the Decline and Fall of the Roman Empire $1 (BVolume 5" by Edward Gibbon is part of a six-volume work published between 1776 and 1788. This monumental history traces the Roman Empire from its peak through the fall of Western Rome, the rise of Christianity as state religion, and the fall of Byzantium. Gibbon argues that Rome succumbed to barbarian invasions largely due to the gradual loss of civic virtue among its citizens, controversially exploring Christianity's role in this decline with detached yet critical prose. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_History_of_the_Decline_and_Fall_of_the_Roman_Empire
Release date is 2008-06-07
David Reed and David Widger
Keywords: Rome -- History -- Empire, 30 B.C.-476 A.D.; Byzantine Empire -- History -- To 527